PERANAN PEK SING TJONG DALAM PERANG KEMERDEKAAN DI TANJUNG BELIT KECAMATAN SIAK KECIL KABUPATEN BENGKALIS TAHUN 1945-1950 - Marlogam Purba; Tugiman. MS Tugiman. MS; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Pek Sing Tjong is a patriot of Chinese descent. Pek Sing Tjong had a role in the independence war in Tanjung Belit in 1945-1950 by smuggling weapons from Singapore to Tanjung Belit. The purpose of this research is to know the character of Pek Sing Tjong in the independence war in Tanjung Belit, To know the role of Tang Kim Teng in the war of independence in Tanjung Belit, To know the end of Tang Pek Sing Tjong struggle in the independence war in Tanjung Belit, To Know the award earned Pek Sing Tjong from Government. The method used in this research is qualitative. Data obtained from the interviews are then analyzed in their own language. The location of the research is Tanjung Belit, district Siak Kecil, Bengkalis. This research started from the beginning of the title of this researcher submitted until this thesis is completed. Data collection techniques used are observation techniques, documentation techniques, interview techniques and literature study techniques. The results showed that Pek Sing Tjong had a role in the independence war in Tanjung Belit by smuggling weapons and supplies from Singapore to Tanjung Belit and forwarded to Bengkalis Regiment IVKeywords: Pek Sing Tjong, Independence, Tanjung Belit